Cyclin-dependent kinase 5 is involved in the phosphorylation of gephyrin and clustering of GABA A receptors at inhibitory synapses of hippocampal neurons - Kalbouneh, Hebah; Schlicksupp, Andrea; Kirsch, Joachim; Kuhse, Jochen (PLOS ONE, 2014)
CDK5 has been implicated in neural functions including growth, neuronal migration, synaptic transmission and plasticity of excitatory chemical synapses. Here we report robust effects of CDK5 on phosphorylation of the postsynaptic scaffold protein gephyrin and clustering of inhibitory GABAA receptors in hippocampal neurons. shRNA-mediated knockdown of CDK5 and pharmacological inhibition of cyclin-dependent kinases reduced phosphorylated gephyrin clusters and postsynaptic γ2-containing GABAA receptors. Phosphorylation of S270 is antagonized by PP1/PP2a phosphatase and site-directed mutagenesis and in vitro phosphorylation experiments indicate that S270 is a putative CDK5 phosphorylation site of gephyrin. Our data suggest that CDK5 plays an essential role for the stability of gephyrin-dependent GABAA receptor clusters in hippocampal neurons.